Youth as consumers in the digital age - María Teresa Díaz Mohedo; Alejandro Vicente Bújez (Revista Electrónica Interuniversitaria de Formación del Profesorado)
With this article we intend to justify the need for an education that encourages adolescents to reflect upon the changes in the construction of knowledge created by the access to new technologies, which are the main cause of excessive consumption in our society today. Firstly, we discuss the ways in which ICTs are influencing the construction of knowledge, and we then focus on the role that families, schools and public administration play in consumer education, which should highlight and respect children’s rights as consumers...